The isolation and identification of the alkaloids of Anona muricata Linne - Librea, Julieta Raymundo 1940-
The present chemical investigation on the stembark of Anoma muricata Linn. involved the isolation of a phenolic base and two nonphenolic bases. The phenolic base was crystallized as perchlorate salt C19 H23 O4 N.HC1 O4, m.p. 206-207(degrees) (absolute alcohol). Analyses of the UV, IR and Mass spectra definitely established the phenolic base to be reticuline. The nonphenolic bases were separated by column chromatography. Crystalline perchlorate salt C20 H23 NO2.HC1 O4, m.p. 195-196(degrees) was prepared from the chloroformic eluates. Analyses of the UV, IR, NMR and Mass spectral determinations clearly established the identity of Base A as atherosperminine. The acetone-chloroformic eluates yielded a base B m.p. 176-177(degrees). The yield was so small to warrant chemical or physical determinations of the structure of the base.